2022
DOI: 10.1111/aogs.14433
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of primiparous womenʼs childbirth experience in labor induction with cervical ripening by balloon catheter or oral misoprostol – a prospective study using a validated childbirth experience questionnaire (CEQ) and visual analogue scale (VAS)

Abstract: Introduction: Primiparity and labor induction, especially when cervical ripening is required, are risk factors for a negative childbirth experience. Our aim was to compare childbirth experience in primiparous women with cervical ripening by balloon catheter or oral misoprostol using the validated Childbirth Experience Questionnaire (CEQ).We also wanted to compare assessment of a negative childbirth experience by visual analogue scale (VAS) and CEQ. Material and methods:This is a prospective study of 362 primip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
5
1
Order By: Relevance
“…Anyhow, there was no significant difference regarding patient satisfaction for this criterion in our study. Our results are consistent with those of Mieke et al [20] , which find no difference between the two methods of cervical ripening on that outcome, and with those of Place et al [18] , which find that 78,3 % of women were satisfied in balloon catheter group and 77,1 % in oral misoprostol group. Recent study of Anjali et al [26] suggests that the association of oral misoprostol and balloon catheter would reduce the time of labor, but no satisfaction outcome were evaluated.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Anyhow, there was no significant difference regarding patient satisfaction for this criterion in our study. Our results are consistent with those of Mieke et al [20] , which find no difference between the two methods of cervical ripening on that outcome, and with those of Place et al [18] , which find that 78,3 % of women were satisfied in balloon catheter group and 77,1 % in oral misoprostol group. Recent study of Anjali et al [26] suggests that the association of oral misoprostol and balloon catheter would reduce the time of labor, but no satisfaction outcome were evaluated.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding time of delivery, Dupuis et al [17] suggested that delivery within 24 h influence positively the maternal satisfaction. It is unclear about which cervical ripening method between balloon catheter or oral misoprostol enables a more rapid delivery, as the different studies seem contradictory [10] , [11] , [18] , [25] . Anyhow, there was no significant difference regarding patient satisfaction for this criterion in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a simple 10-point VAS to measure the childbirth experience, which does not cover the multidimensional and subjective experience of childbirth but offers a simplified means to assess the overall childbirth experience. Furthermore, prior literature shows that VAS sufficiently measures the childbirth experience14 24–27 and correlates with more detailed measures of the childbirth experience 14 24 28. A lack of demographic and socioeconomic data in our study limited the possibility of studying the impact of these factors on subsequent childbirth, although microlevel indicators based on these discrepancies have been shown to influence on entire maternal care continuum 29.…”
Section: Discussionmentioning
confidence: 87%